A Narrative Inquiry on the Teachers’ Sense of Plausibility of an Experienced Malaysian English Language Teacher - Jayakaran Mukundan; Hui Geng; Vahid Nimehchisalem (Humanities & Social Sciences Communications)
Abstract Teachers’ Sense of Plausibility (TSOP) is a state of knowledge of teachers about teaching that develops out of experience. Teachers seem to modify their knowledge of teaching when they are faced with challenges within their own unique work surroundings. The present study investigated the TSOP of one secondary school English Language Teacher, an Expert Teacher with 30 years of classroom teaching experience. This qualitative study is a narrative inquiry. Data was collected through a questionnaire, interviews and field notes. The synergies among the three modes of data collection were evident in their overlap, leading to triangulation. The lead researcher had kept notes from 2014 in the many encounters with the subject while they were on joint teacher appraisals. This helped strengthen evidence from the questionnaire and interviews. Through a timeline, the nature and characteristics of the subject’s TSOP across 30 years were first investigated and mapped by the researchers. Subsequently, the subject’s TSOP was compared to the five-descriptor TSOP Framework developed for Experienced and Accomplished Educators (EAE). The findings revealed that there were four distinct TSOP phases for this subject. The study also revealed more similarities than differences between this subject and the 20 in the EAE group. This research would benefit the field of Teacher Professional Development (TPD) considerably as it would determine if there are critical, differentiated phases in an educator’s TSOP, and if there are common characteristics that determine competence in educators, no matter what level they teach. Methodologically, the investigation and description of 30 years of a teacher’s life in terms of evolving TSOP would be considered a major contribution worthy of replication in future studies. Then the comparative nature of this study (academics versus school teachers) provides evidence that accomplished academics and teachers may have a lot more similarities than differences.